Space as a Competition Domain: Threats and Opportunities - D. V. Stefanovich; D. Porras (Международная аналитика, 2022)
The article deals with the unfolding race for military, technological, and political infl uence in space. Great powers have competed in space since the dawn of the Space Age. Today we are once again faced with the possibility of space warfi ghting, but there are more than two players in the game now and civil infrastructure depends on space more than ever before. Theoretical space war threats are often analysed through an assessment of possible targets. And there are real-life challenges and threats here, including but not limited to rendezvous and proximity operations (RPO), existing destructive anti-satellite (ASAT) capabilities, non-destructive electronic warfare, and cyber and jamming capabilities. The greatest threat, though, comes from simple misperceptions of actions in space by diff erent actors. Space cannot be separated from dynamics on Earth, but there might be some room for space-specifi c confi dence-building, risk reduction and even arms control measures.